MODERN MECHANISMS FOR INCREASING THE INVESTMENT ATTRACTIVENESS OF REGIONS (Academicia Globe: Inderscience Research, 2026)
The increasing competition among regions for investment resources necessitates the development and implementation of effective mechanisms aimed at enhancing regional investment attractiveness. This study examines the theoretical and practical aspects of modern approaches used to improve the investment climate of regions. The research analyzes the role of institutional reforms, digital transformation, infrastructure development, innovation ecosystems, public-private partnerships, and special economic zones in attracting domestic and foreign investments. Particular attention is given to the influence of governance quality, business environment conditions, and technological modernization on regional competitiveness. The study employs comparative, analytical, and systematic research methods to identify the most effective mechanisms for increasing investment attractiveness. The findings indicate that the integration of digital technologies, transparent governance systems, and innovation-oriented development strategies significantly contributes to attracting investment flows and ensuring sustainable regional economic growth. The research results may serve as a basis for policymakers and regional authorities in designing strategies aimed at strengthening regional competitiveness and improving investment performance.